(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objectives: This research aimed to determine the optimum type of solvent and extraction time to produce secondary metabolites (phenolics, flavonoids, tannins, and antioxidants) from mangosteen leaves (Garcinia mangostana L.) as feed additive candidates for poultry. Materials and Methods: This research used a completely randomized design with a 2 × 5 factorial design with three replications. Factor A used two types of distilled water as a solvent (ordinary distilled water and distilled water heated at 100°C), while Factor B encompassed various extraction times (15, 30, 45, 60, and 75 min). The parameters assessed included total phenolic content (TPC), total flavonoid content (TFC), total tannin content (TTC), and overall antioxidant activity. Results: The TPC, TFC, TTC, and total antioxidant activity all showed a highly significant interaction (p < 0.01) with the type of solvent and extraction duration. Conclusion: The best solvent and time for mangosteen leaf extract to produce secondary metabolites, which can be candidates for feed additives in poultry, is ordinary distilled water for 45 min. In this research, the phenol content was 81.03%, flavonoids 11.07%, tannins 1.01%, and antioxidants 77.61%. Adv. Vet. Anim. Res., 11(1): 139-145, March 2024 http://doi.org/10.5455/javar.2024.k758